The Effect of Promotionl Mix in Increasing The Market Share (Case study of the Syrian Commercial Bank, Hama Branch) (Journal of Hama University, 2021)
This study aimed to find out the impact of the promotional mix applied in banks on the market share by analyzing and discussing the impact of each of the promotional mix elements and the promotional mix strategy on the market share, and under the assumption that there is a statistically significant effect for each of the independent variables) the elements of the promotional mix, the mix strategy Promotional (in the dependent variable) market share) using the simple regression analysis method to study the relationship between each independent variable and the dependent variable and using the multiple regression analysis method to study the effect of the independent variables collectively on the dependent variable, depending on the statistical analysis program SPSS, The study concluded that there is a statistically significant relationship for each of (promotional mix elements and promotional mix strategy) with the market share, and the study reached conclusions, including: that the commercial bank uses several tools from the elements of the promotional mix to ensure the definition of traditional and new services, attract new customers and enhance the relationship with customers. It shows the importance of interest and the use and application of modern promotional means in order to reach the various customer segments and attract them to request services and thus expand the market share according to the strategy and goals that the organization seeks.